The Effect of Storytelling Method Using Big Book in Improving Children's Learning Concentration in Kindergarten - Novita Prima Zola; Nurhafizah Nurhafizah (EduBasic Journal: Jurnal Pendidikan Dasar, 2021)
This article is motivated by the research results revealing the low children's learning concentration in Insan Bangsa Kindergarten. It was caused by the unattractiveness of the learning media provided by the teacher. For this reason, this study aims to see the effect of the storytelling method using Big Book in improving children's learning concentration in Insan Bangsa Kindergarten. The Big Book was chosen to increase children's learning concentration since it has the advantage of highlighting the colors and pictures in the book to make students interested in books and concentrate when studying. This study used quantitative research methods, namely quasi-experimental. The samples in this study were group B2 with ten children as the experimental class and group B1 with ten children as the control class. The sampling technique used in this research was purposive sampling, and data collection employed observation. The research data were then analyzed utilizing the SPSS type 17 application. The results of this study revealed that t-count t-table, namely 2.386 2.101, so it can be said that the hypothesis Ha was accepted or H0 was rejected. This study concludes that the storytelling method using the Big Book significantly improved children's learning concentration in Insan Bangsa Kindergarten. It was obtained from the children's learning concentration level, which was higher than before using Big Book.